(untitled) (Eurasian Journal of Ecology, 2016)
Potential of tourism development in Kazakhstan, including the area of Korgalzhyn in Akmola region is discussed in the article. Activity of UNDP in Kazakhstan and the Information and Resource Center for tourism of the Korgalzhyn area is considered.